Effects of individualized follow-up with a smartphone-application after cardiac rehabilitation: protocol of a randomized controlled trial - Pernille Lunde; Asta Bye; Astrid Bergland; Birgitta Blakstad Nilsson (BMC, 2019)
Abstract Background Cardiac rehabilitation (CR) programs are evidence-based and widely recommended. However, benefits from CR are likely lost among individuals who discontinue their regular exercise routines and healthy habits. One possible approach to enhance adherence to lifestyle advice after completion of CR, may be individualized follow-up enabled by a smartphone application (app). Methods A protocol of a single-blinded, pragmatic randomized controlled trial. The study will take place in the eastern part of Norway, and will include heart patients who have completed CR. Participants will be recruited from two CR centers. Based on power calculation, 113 participants will be included. The intervention group will receive individualized follow-up through an app on a weekly basis throughout a year. The app will be set up with the participant's own goals, and the follow-up will be based on these individual goals. The control group will receive usual care, including general advice regarding physical activity, exercise and diet. The participants will be assessed at baseline (at completion of CR) and 12 months after baseline. Primary outcome of the study will be peak oxygen uptake. Secondary outcomes include exercise performance, quality of life, health status, health literacy, self-perceived goal achievement, exercise habits, body weight, blood pressure as well as lipids and triglycerides. Discussion To our knowledge, this will be the first study to examine the effects of individualized follow-up with an app for one year, in patients completing CR. Hence, it is reasonable to assume that the study may be groundbreaking. Due to the large sample size and the theoretically based intervention, the study has the potential to generate new knowledge that may improve the design of future technology-based follow-up interventions of patients that have completed rehabilitation. Trial registration ClinicalTrials.gov. NCT03174106. First registration, 19/05/2017.